MANUSIA PELAKU DARI ANTROPOSENTRISME MANUSIA DAN ALAM SEMESTA - I Made Arika Dharma Kusuma (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
Humans are creatures that are the center of the earth and mangula is often referred to in environmentalethical theory as humans are positioned tobe the central being son earth, but sometimes in anthropocentrism thinking it gives preservation to the universe but humans can also destroy or dissolve all universes with their advantages so that human needs and desires which is fulfilled without looking at the damaged environment, but humans can also preserve the universe as a whole, in Hindu religious teachings which are included in the teachings of the Hinducosmological concept interms of the creation of the entire universe.Cosmology is one of the important knowledge in Hinduism, because cosmology not only provides knowledge about the creation of the universe, further more cosmology can explain the true nature of human beings,which has so far been difficult to understand.Cosmological teachings in Bali are written down in local theology. In particular, lontars or Shivaistic texts always put forward the teachings or knowledge of God (Stwa)and knowledge of the path to attaining Himand the creation of the universe,be it bhuana agung or bhuana alit.For this reason, true knowledge and proper implementation of concepts are also needed it is especially important to put forward the concept of Hindu cosmology in the Bhuana Kosa text on the correct understanding in everyday life burning a harmonious life and increasing devotion to God.